Comparative genomic analysis of the aldehyde dehydrogenase gene superfamily in Arabidopsis thaliana – searching for the functional key to hypoxia tolerance - Guan, Yufeng; Tanwar, Umesh Kumar; Sobieszczuk-Nowicka, Ewa; Floryszak-Wieczorek, Jolanta; Arasimowicz-Jelonek, Magdalena (Frontiers in Plant Science, 2022)
Flooding entails different stressful conditions leading to low oxygen availability for respiration and as a result plants experience hypoxia. Stress imposed by hypoxia affects cellular metabolism, including the formation of toxic metabolites that dramatically reduce crop productivity. Aldehyde dehydrogenases (ALDHs) are a group of enzymes participating in various aspects of plant growth, development and stress responses. Although we have knowledge concerning the multiple functionalities of ALDHs in tolerance to various stresses, the engagement of ALDH in plant metabolism adjustment to hypoxia is poorly recognized. Therefore, we explored the ALDH gene superfamily in the model plant Arabidopsis thaliana. Genome-wide analyses revealed that 16 AtALDH genes are organized into ten families and distributed irregularly across Arabidopsis 5 chromosomes. According to evolutionary relationship studies from different plant species, the ALDH gene superfamily is highly conserved. AtALDH2 and ALDH3 are the most numerous families in plants, while ALDH18 was found to be the most distantly related. The analysis of cis-acting elements in promoters of AtALDHs indicated that AtALDHs participate in responses to light, phytohormones and abiotic stresses. Expression profile analysis derived from qRT-PCR showed the AtALDH2B7, AtALDH3H1 and AtALDH5F1 genes as the most responsive to hypoxia stress. In addition, the expression of AtALDH18B1, AtALDH18B2, AtALDH2B4, and AtALDH10A8 was highly altered during the post-hypoxia-reoxygenation phase. Taken together, we provide comprehensive functional information on the ALDH gene superfamily in Arabidopsis during hypoxia stress and highlight ALDHs as a functional element of hypoxic systemic responses. These findings might help develop a framework for application in the genetic improvement of crop plants.